PERAN PEREMPUAN DALAM MENINGKATKAN PENDAPATAN EKONOMI RUMAH TANGGA NELAYAN DIKELURAHAN MANGGAR BARU BALIKPAPAN - Dea Karina; Tri Astuti Nuraini; Prita Indriawati (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2018)
Uncertainty of income obtained by the head of the family as a fisherman encourages the housewife member of the fisherman to work in order to fulfill the household's living needs. This research was conducted to determine the role of women in increasing the economic income of fishermen households in Manggar Baru Balikpapan and also to find out what obstacles faced by women in increasing the economic income of fishermen households. This research was also conducted to determine government policies in empowering coastal women. This research method uses descriptive qualitative methods. Data from this study were obtained by observing, interviewing, and documenting studies and processed using source triangulation techniques. The results of this study indicate that the role of women in increasing the economic income of fishermen households taking care of the household is a top priority, accompanying their husbands, taking care of their children and helping their husbands work as crab skin peelers or running small shops can increase household economic income. In carrying out this role they did not escape the obstacles they faced, the obstacles faced by women in increasing the economic income of fishermen households were the constraints of unhygienic and unsafe water sources for individual and household needs as well as the absence of strengthening women fishermen groups for small business industries is a constraint faced by women in increasing household economic income. In terms of empowering coastal communities, the Government participates in conducting coaching for coastal communities in the Manggar Baru Balikpapan village through trainings even though the training is not regularly scheduled.